Sport policy and multilevel governance: A case study of Ontario and Quebec - Rose, Michelle (University of Ottawa (Canada), 2006)
The introduction of the new Canadian Sport Policy in 2002 included Enhanced Interaction as one of its four goals. This study examines how interaction between governments and civil society has evolved from the 1990s to the present to determine how the Canadian Sport Policy has influenced multilevel governance in sport. Using both semi-structured interviews and a document analysis, this study looked at sport policies from the governments of Canada, Quebec and Ontario and the cities of Montreal and Toronto to identify the nature of their interactions with each other and civil society. Using the Advocacy Coalition Framework (ACF) to examine these interactions and their effects on policy change, the findings revealed that although multilevel governance was long considered a priority for the success of Canadian sport, it was not until the introduction of the Canadian Sport Policy that interaction on a multilevel was formalized. Recommendations are also offered to further enhance multilevel governance in Canadian sport and improve policy implementation.
Keywords: Health Sciences, Recreation.; Recreation.